PENATALAKSANAAN MIGREN PADA ANAK - Tri Makmur (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2018)
Headache is the biggest part of human suffering that is often found not only in adults, but also inchildren. The prevalence of migraines in adult men is 9% and women are 18%, while in childrenaged 7 years the prevalence is 1.2-3.2%, and between the ages of 7-15 years ranges between 4-11%. Migraine attacks can be precipitated by certain foods that contain thyramin such as cheese,meat (hogdog and bacon), chocolate containing phenylthylamine, additives in foods such asmonosodium glutamate. Many theories have been proposed, one of which is the vascular theory ofmigraine pathophysiology which describes that the occurrence of migraine attacks includes 2phases. Migraine diagnosis is based on history, clinical observation and does not require diagnostictests. In diagnosing migraine in children, diagnostic criteria are generally used. Migraine treatmentis symptomatic. Patients and their families are informed about factors that can trigger migraineattacks and that attacks can be reduced through regular living and avoiding triggers. Generallymigraine attacks must be treated if the frequency of attacks is frequent and sufficient to influencethe child's activity. Short-term prognosis in children with migraines is more than 50% of patientsreport improvement within 6 months after treatment, while the long-term prognosis gets 2/3 ofchildren will experience remission within 2 years or more.